Triterpene benzoates from the bark of Picramnia teapensis (Simaroubaceae) - Rodriguez-Gamboa, T.; Fernandes, J. B.; Rodrigues, E.; da Silva, MFDF; Vieira, P. C.; Barrios, M.; Castro-Castillo, O.; Victor, SR; Pagnocca, F. C.; Bueno, O. C.; Hebling, MJA (Soc Brasileira Quimica, 2001)
Two new benzoic acid esters of triterpene alcohols [lup-20 (29)-en-28-oic acid 3 alpha, 7 beta -dibenzoate and 3 alpha -hydroxy-lup-20(29)-en-28-ic acid 7 beta -benzoate] were isolated from the stem bark of Picramnia teapensis Tul. The structures of these compounds were established on the basis of spectral analyses. Other known compounds, beta -sitosterol, estigmasterol, lupeol and epilupeol, were identified in mixture by GC-MS. The triterpene esters have not shown in-vitro inhibitory effect on the growth of Leucoagaricus gongylophorus (Fisher), referred also as Leucocoprinus gongylophorus (Heim), syn Rozites gongylophora (Moller), the symbiotic fungus cultivated by the leaf-cutting ant Atta sexdens L.
Keywords: triterpene esters; lupanes; Picramnia teapensis; Atta sexdens; Leucoagaricus; gongylophorus